2011
DOI: 10.1111/j.1755-3768.2011.02274.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the corneal biomechanical properties with the Ocular Response Analyzer® (ORA) in African and Caucasian normal subjects and patients with glaucoma

Abstract: ABSTRACT.Purpose: To compare corneal hysteresis (CH) and corneal resistance factor (CRF) measured with the Ocular Response Analyzer Ò tonometer (ORA) between (i) African normals and treated primary open-angle glaucoma (POAG) patients and (ii) between normals and treated POAG Caucasians. To analyse the correlation of CH and CRF with visual field (VF) defects in the two groups.Methods: This comparative study included 59 African (29 (POAG), 30 normals) and 55 Caucasians (30 POAG and 25 normals) subjects. Goldm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
7
20
0
1
Order By: Relevance
“…With greater statistical power in the present study, it was not surprising that we observed a significant difference in CH between blacks and whites that was independent of CCT. This result is similar to that of Detry‐Morel and colleagues who observed lower average CH values in Africans compared with Caucasians and found this relationship to exist independent of CCT in both healthy and glaucomatous eyes (Detry‐Morel et al. 2011).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With greater statistical power in the present study, it was not surprising that we observed a significant difference in CH between blacks and whites that was independent of CCT. This result is similar to that of Detry‐Morel and colleagues who observed lower average CH values in Africans compared with Caucasians and found this relationship to exist independent of CCT in both healthy and glaucomatous eyes (Detry‐Morel et al. 2011).…”
Section: Discussionsupporting
confidence: 91%
“…2011). However, their sample size was relatively small, and given that 75% of their African subjects were natives of Congo, the external validity of the results is limited for many clinicians (Detry‐Morel et al. 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study did not assess biomechanical properties such as corneal hysteresis as a complement to CCT measurements. These may affect CLS readings, and therefore, further research including assessment of corneal hysteresis may be of interest (Alhamad & Meek 2011), (Detry‐Morel et al. 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some studies reported the lack of association between CH and both GAT and IOPg [30, 64, 65], suggesting that CH is independent of IOP, while other studies suggest a relationship between CH and IOP. CH has been shown to decrease as the IOPcc increases [30, 46, 66, 67]. Kamiya et al [66] found IOP as a significant explanatory variable relevant to CH, while González-Meijome et al [68] found a significant correlation between changes in IOP and changes in CH during the day in healthy eyes.…”
Section: Factors Affecting Corneal Biomechanical Propertiesmentioning
confidence: 99%